Rancang Bangun Smart Dispenser Dengan RFID Berbasis Arduino - Nurhasanah, Rizki (Electrical Network Systems and Sources, 2025)
The water supply arrangement in the TRSE Laboratory at Politeknik Negeri Pontianak needs to be improved to address the rapid depletion of water.  An Arduino-based smart dispenser was developed with an RFID sensor for user identification and water usage recording, as well as a proximity sensor to ensure the presence of a container before water is dispensed.  This system is equipped with a keypad for selecting the volume of water and an LCD to display the daily quota of 700 ml.  The pump automatically shuts off when the quota is exhausted or the container is not detected.  Testing shows that the system limits water usage according to the quota, with an average error of 6% (100 ml) to 0.857% (700 ml).  Accuracy increases with larger volumes, ensuring more efficient water distribution.  This smart dispenser becomes an effective solution in water management in the laboratory. Keywords: Smart Dispenser, Arduino, RFID Sensor, Proximity Sensor.